2009
DOI: 10.1007/s11666-009-9372-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of TGO Composition on the Thermal Shock Lifetime of Thermal Barrier Coatings with Cold-sprayed MCrAlY Bond Coat

Abstract: NiCoCrAlTaY bond coat was deposited by cold spraying to assemble thermal barrier coatings (TBCs). The microstructure of the cold-sprayed bond coat was examined using scanning electron microscopy. TBCs consisting of cold-sprayed bond coat and plasma-sprayed YSZ were pretreated at different conditions to form different thermally grown oxides (TGOs) before thermal cycling test. The influence of the TGO composition on the thermal cyclic lifetime was quantitatively examined through the measurement of the coverage r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(42 citation statements)
references
References 39 publications
2
33
0
3
Order By: Relevance
“…Cold spraying is also being investigated to deposit MCrAlY coating (Ref [24][25][26][27]. A cold-sprayed coating is formed through the plastic deformation upon the impact of sprayed particles at a temperature well below the melting point of the spray material, which makes the cold spraying become an alternative method to deposit a dense MCrAlY bond coat in thermal barrier coatings without oxidation (Ref [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Cold spraying is also being investigated to deposit MCrAlY coating (Ref [24][25][26][27]. A cold-sprayed coating is formed through the plastic deformation upon the impact of sprayed particles at a temperature well below the melting point of the spray material, which makes the cold spraying become an alternative method to deposit a dense MCrAlY bond coat in thermal barrier coatings without oxidation (Ref [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Em função de tais características, diversas pesquisas têm sido realizadas utilizando estes métodos de aplicação [35][36][37][38]. Os resultados são, em geral, promissores, encontrando aplicação rela em diversos segmentos.…”
Section: Desenvolvimentos Desafios E Perspectivasunclassified
“…Como a oxidação da camada de ligação, típica dos TBC's em serviço, afeta especialmente a vida dos revestimentos, causando sua delaminação, diversos estudos vêm sendo atualmente efetuados nesta linha, buscando maior entendimento do processo em si e da variação ocasionada por este processo nas tensões e morfologia da interface [35,[58][59][60][61][62][63][64].…”
Section: Oxidação Em Alta Temperatura E Outros Fatores Adicionaisunclassified
“…It has been reported that Al 2 O 3 exhibits better adhesion to YSZ coatings and a lower growth rate than other oxides, such as NiO, Cr 2 O 3 , and spinel. 4,13) Ni/Cr mixed oxides in TGOs grow rapidly, resulting in high volumetric expansion stress in the YSZ coating, 4,14) which promotes the failure of TBCs. The continuous and uniform alumina-based TGO formed on the cold-sprayed bond coat protects the bond coat from fast oxidation.…”
Section: Oxidation Behavior Of Ni-conicraly Coatingsmentioning
confidence: 99%